2017
DOI: 10.1089/jop.2017.0019
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Combined Tear Film Therapy in Patients with Evaporative Dry Eye with Short Tear Film Breakup Time

Abstract: Mucin or lipid-targeting agents combined with aqueous supplements in patients with refractory EDE with short TBUT might improve subjective symptoms and TBUT. Of this, targeting whole tear film layers was most effective in improving ocular symptoms and tear film quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 57 publications
1
12
0
1
Order By: Relevance
“…Thus far, only a few studies, mostly in Japan and some in Korea, have been performed on this condition. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]…”
Section: Recent Progress Around the Worldmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, only a few studies, mostly in Japan and some in Korea, have been performed on this condition. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]…”
Section: Recent Progress Around the Worldmentioning
confidence: 99%
“…Since the first report in 1995, many more papers have been added to the literature describing short TBUT-type dry eye, and this number is expected to increase, especially in Asia. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]36 Although this type of dry eye has been considered relatively mild to moderate because of the limited abnormality of ocular surface, recently Kim et al reported that the prevalence of depression among dry eye patients is higher in the mild type of dry eye, which overlaps with the short TBUT-type dry eye. 37,38 The precise prevalence of short TBUT-type dry eye is unclear, but TBUT is expected to be high according to a study among office workers in Osaka.…”
Section: History Of the Short Tbut-type Dry Eyementioning
confidence: 99%
“…The mean reduction in the OSDI sum score was À23% in 10 days and À53% in 30 days, clearly reflecting time dependence. Improvements by 25 OSDI units have usually not been achieved in randomized clinical trials within similar time frames (Essa et al 2018;Fariselli et al 2018;Kim et al 2017). The observed change of 2.6 times the MCID (Miller et al 2010;Wolffsohn et al 2017) demonstrates the SIME and control formulations capable of reducing symptoms to a clinically meaningful extent that can be noticed by the patient.…”
Section: Discussionmentioning
confidence: 96%
“…There were several treatments to improve the quality of the Meibomian gland in the past, including warm compresses and improved eyelid hygiene, as well as antibiotic and anti-inflammatory agents. To overcome the shortcomings of the above, there are more options for the treatment of dysfunction of Meibomian gland currently, such as intraductal Meibomian gland probing, emulsion eye drops containing lipids, thermal pulsation system, and intense pulsed light therapy [74][75][76][77][78]. One systemic review also confirmed that a single 12-min vectored thermal pulsation was more efficient than traditional warm compression for DED in both objective or subjective measurements.…”
Section: Lipid Anomaly Dry Eye (Lade)mentioning
confidence: 99%